The Effect of Hawaii’s Ban The Box Law on Repeat Offending - D’Alessio, Stewart J. (American journal of criminal justice, 2015)
The social stigma accompanying an official criminal record hinders the ability of an individual to acquire quality and stable employment, which is problematic because of the often reported nexus between unemployment and criminal behavior. Ban the box laws that limit an employer’s use of criminal background checks during the hiring process are being established across the country to help integrate ex-offenders into the labor force. The current study investigates whether Hawaii’s 1998 ban the box law reduced repeat offending in Honolulu County. Logistic regression results show that a criminal defendant prosecuted in Honolulu for a felony crime was 57 % less likely to have a prior criminal conviction after the implementation of Hawaii’s ban the box law. By mollifying the social stigma attached to a criminal record during the hiring process, Hawaii’s ban the box law proved to be extremely successful in attenuating repeat felony offending.